AKTIVITAS ANTIFUNGAL MINYAK ATSIRI JINTEN PUTIH TERHADAP Candida parapsilosis SS25, C. orthopsilosis NN14, C. metapsilosis MP27, DAN C. etchellsii MP18 - Ridawati, Ridawati; Jenie, Betty Sri Laksmi; Djuwita, Ita; Sjamsuridzal, Wellyzar (UI Scholars Hub, 2011)
Antifungal Activity of Cumin Oil Against Candida parapsilosis SS25, C. orthopsilosis NN14, C. metapsilosis MP27, and C. etchellsii MP18. Many kinds of spices are used in Indonesia, one of them is white cumin seed. This spice is used not only for cooking, but also for traditional medicine. This study reported of antifungal activity from white cumin’s essential oil. Extraction and identification of Cumin oil were carried out. We obtained 2.5-3.0% of white essential oil which was colorless or light yellow color. GCMS analysis revealed that there were 12 peaks. Based on peak’s intensity the oil were dominated by 4 compound i.e. cuminaldehide (35.44%), ρ-cymene (34.77%), β-pynene (15.08 %) and γ-terpinene (8.15%). Growth inhibition zone determination has been carried out by diffusion disc and direct method against yeast i.e. C. parapsilosis SS25, C. orthopsilosis NN14, C. metapsilosis MP27, and C. etchellsii MP18. The results showed that all of the yeasts were sensitive to cumin oil. The inhibition zone radius were 13.4-16.5 mm. The cumin oil showed the inhibition of yeast growth with MIC values of 0.028%-0.042% and MFC values 0.09%- 0.14%, while nystatin had MIC values 0.40%-0.50% and MFC values 3.0%-4.0%. The activity of cumin oil was very strong as antifungal.